A SIMPLE METHOD ESTIMATES AND ECONOMIC INDICATORS OF PHOTOVOLTAIC SYSTEMS FOR DRIP IRRIGATION - A. Gajić, Boško; P. Tomić, Zorica; J. Sredojević, Zorica (Economics of Agriculture, 2013)
Renewable, environment friendly, photovoltaic (PV) solar energy have been one of the most attractive means for pumping the water needed to irrigate crops. However, since at the present time PV systems still suffer from high investment costs it is necessary to accurately dimension the installations. This study presents a simple but accurate a process to estimate the required dimension of a photovoltaic installation designed to power a pumping system for the drip irrigation of a raspberry plantation in W Serbia. The methodology is based on systematic approach to the problem, taking into account all relevant elements, from PV pumping system, local climate, soil properties, depth of well, characteristics of the crop, to irrigation system. With an array of 579 Wp it was found that the system is able to irrigate, without deficit of water, 1.0 ha raspberry plantation. The methodology presented here is applicable for a range of crop areas, and a variety of crop types in regions of similar climate, soil and latitude. Besides the advantages for the environment, since it uses a renewable energy, a study on the economic viability of a photovoltaic system shows that it is similar to conventional systems which use a generator unit. Moreover, the high price of fossil fuels guarantees a progressive advantage of photovoltaic systems.